Le manuscrit arabe et ses papiers - Geneviève Humbert (Revue des Mondes Musulmans et de la Méditerranée)
Paper is an important element by which to date and localize Arabic manuscripts. Inversely, Arabic manuscripts are themselves important for the history of paper since they have been copied on numerous varieties of paper which came from the most diverse places Chinese and Sogdian paper, paper of Italian watermarked type, paper made in Samarkand (and the area of Khurasan in general) as well as from Baghdad, Syria, Yemen, Egypt, Morocco, the Iberian peninsula, Anatolia, Persia, Central Asia, India, Indonesia, etc. It is also important to distinguish between paper used for books – which is the best studied – and paper used by central administrations and chancellery offices whose distribution was perhaps controlled and which may have had their own paper manufacturers.